KEMISKINAN DAN KESENJANGAN PENDAPATAN: PERAN PDRB DAN ZAKAT DI PROVINSI ACEH - Amri Amri; Dara Meutia; Ridwan Nurdin (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2021)
This study aimed to determine the Gross Domestic Product (GDP) and the realization of zakat fund distribution toward the alleviation of poverty and income inequality in Aceh Province. This research involved panel data that is a combination of cross section data and time series data with the number of observation as many as 184 consisted of 23 districts/cities in a period of 8 years (2010 to 2017). This study used two models with dependent variables were the poverty and the income inequality. The result of the poverty model showed that Gross Domestic Product (GDP) and zakat influenced negatively and significantly toward the poverty in Aceh Province. However, the result of income inequality model showed that Gross Domestic Product (GDP) influenced positively and significantly toward the income inequality, whereas zakat influenced negatively but not significantly toward the income inequality. Therefore, it is expected that the government and Baitul Mal Aceh Province to increase the number of Gross Domestic Product (GDP) and zakat as well as to maximize its distribution so that the level of the poverty and the income inequality in Aceh Province can be reduced.Keywords: Poverty, Income Inequality, Zakat, Gross Domestic Product (GDP).AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh Produk Domestik Regional Bruto (PDRB) dan realisasi penyaluran dana zakat terhadap penurunan kemiskinan dan kesenjangan pendapatan di Provinsi Aceh. Penelitian ini menggunakan data panel, yakni gabungan data cross section dan time series dengan jumlah observasi sebanyak 184 yang terdiri atas 23 kabupaten/kota dalam kurun waktu 8 tahun (2010-2017). Penelitian menggunakan dua model dengan variabel terikat yaitu kemiskinan dan kesenjangan pendapatan. Hasil penelitian untuk model mengenai kemiskinan menunjukkan bahwa, PDRB dan zakat berpengaruh negatif dan signifikan terhadap kemiskinan di Provinsi Aceh. Namun, hasil penelitian untuk model mengenai kesenjangan pendapatan menunjukkan bahwa, PDRB berpengaruh positif dan signifikan terhadap kesenjangan pendapatan, sedangkan zakat berpengaruh negatif namun tidak signifikan terhadap kesenjangan pendapatan di Provinsi Aceh. Diharapkan kepada pihak pemerintah dan pihak Baitul Mal Provinsi Aceh untuk dapat lebih meningkatkan jumlah PDRB dan zakat serta memaksimalkan penyalurannya, sehingga tingkat kemiskinan dan kesenjangan pendapatan di Provinsi Aceh dapat semakin dikurangi.Kata Kunci: Kemiskinan, Kesenjangan Pendapatan, Zakat, Produk Domestik  Regional Bruto (PDRB).